2003
DOI: 10.2741/1139
|View full text |Cite
|
Sign up to set email alerts
|

Urinary saturation and risk factors for calcium oxalate stone disease based on spot and 24-hour urine specimens

Abstract: In 222 random spot urine specimens, the calcium concentration and calcium oxalate saturation [DG(CaOx)] were significantly higher among stone formers than among non-stone formers, while the citrate and creatinine-corrected citrate concentrations were lower. In 188 24-hour urine specimens, magnesium excretion was lower among stone formers than non-stone formers, while the creatinine-corrected calcium concentration and DG(CaOx) were higher. Among stone formers, there was no gender difference in the urinary conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…demonstrated that 24‐h urinary citrate excretion was not positively associated with calcium oxalate supersaturation (DG[CaOx]). In contrast, hypercalciuria or hyperoxaluria was fairly common in critically supersaturated urine 25 . They concluded that hypocitraturia alone is not a good predictor of urinary calcium oxalate supersaturation, but it may be associated with the underlying etiological condition.…”
Section: Discussionmentioning
confidence: 98%
“…demonstrated that 24‐h urinary citrate excretion was not positively associated with calcium oxalate supersaturation (DG[CaOx]). In contrast, hypercalciuria or hyperoxaluria was fairly common in critically supersaturated urine 25 . They concluded that hypocitraturia alone is not a good predictor of urinary calcium oxalate supersaturation, but it may be associated with the underlying etiological condition.…”
Section: Discussionmentioning
confidence: 98%
“…Although with some exceptions, patients with calcium urolithiasis generally excrete more lithogenic (calcium, oxalate) and less stone-inhibitory substances (citrate, magnesium) in urine than healthy individuals, no single urinary parameter is able to discriminate these two groups sufficiently [6,10,22,23], partially because stoneformers constitute an extremely heterogeneous group with respect to urolithiasis etiology. In terms of metabolic factors, typical lithogenic abnormalities, such as hypercalciuria, hyperoxaluria, or hypocitraturia, occur in different proportions and only in a portion of all patients.…”
Section: Discussionmentioning
confidence: 94%
“…This has proved to be successful as creatinine-corrected calcium and citrate concentrations in early morning urine have been shown to be a substitute for 24-h excretion of these analytes [25]. However, the creatinine ratios for Ox, Mg and UA are not accurate predictors of 24-h excretions [25] but are nevertheless widely used for standardizing concentrations in non-24-h urine collections. Accordingly, urine concentrations were adjusted against creatinine by computing the ratios Ca/Cr, Ox/Cr, Mg/Cr, Cit/Cr and urate/Cr.…”
Section: Urine Samplesmentioning
confidence: 97%
“…Since spot urine concentrations are known to be highly dependent on fluid intake, such measurements are adjusted for creatinine owing to its relatively constant excretion throughout the day, and within and across populations [24]. This has proved to be successful as creatinine-corrected calcium and citrate concentrations in early morning urine have been shown to be a substitute for 24-h excretion of these analytes [25]. However, the creatinine ratios for Ox, Mg and UA are not accurate predictors of 24-h excretions [25] but are nevertheless widely used for standardizing concentrations in non-24-h urine collections.…”
Section: Urine Samplesmentioning
confidence: 98%